In situ extractive fermentation for the production of hexanoic acid from galactitol by Clostridium sp BS-1 - Jeon, Byoung Seung; Moon, Chuloo; Kim, Byung-Chun; Kim, Hyunook; Um, Youngsoon; Sang, Byoung-In (Elsevier BV, 2013)
Clostridium sp. BS-1 produces hexanoic acid as a metabolite using galactitol and enhanced hexanoic acid production was obtained by in situ extractive fermentation with Clostridium sp. BS-1 under an optimized medium composition. For medium optimization, five ingredients were selected as variables, and among them yeast extract, tryptone, and sodium butyrate were selected as significant variables according to a fractional factorial experimental design, a steepest ascent experimental design, and a Box-Behnken experimental design. The optimized medium had the following compositions in modified Clostridium acetobutyricum (mCAB) medium: 15.5 g L-1 of yeast extract, 10.13 g L-1 of tryptone, 0.04 g L-1 of FeSO4 center dot 7H(2)O, 0.85 g L-1 of sodium acetate, and 6.47 g L-1 of sodium butyrate. The predicted concentration of hexanoic acid with the optimized medium was 6.98 g L-1, and this was validated experimentally by producing 6.96 g L-1 of hexanoic acid with Clostridium sp. BS-1 under the optimized conditions. In situ extractive fermentation for hexanoic acid removal was then applied in a batch culture system with the optimized medium and 10% (v/v) alamine 336 in oleyl alcohol as an extractive solvent. The pH of the culture in the extractive fermentation was maintained at 5.4-5.6 by an acid balance between production and retrieval by extraction. During a 16 day culture, the hexanoic acid concentration in the solvent increased to 32 g L-1 while it was maintained in a range of 1-2 g L-1 in the medium. The maximum rate of hexanoic acid production was 0.34 g L-1 h(-1) in in situ extractive fermentation. (C) 2013 Published by Elsevier Inc.